Naturally developed HPV16 antibodies and risk of newly detected cervical HPV infection outcomes - Trevisan, Andrea; Candeias, João M. G. [UNESP]; Thomann, Patrícia; Villa, Luisa L.; Franco, Eduardo L.; Trottier, Helen (Wiley, 2024)
Little is known about the protection conferred by antibodies from natural human papillomavirus (HPV) infection. Our objective was to evaluate the association between HPV16 seroreactivity and HPV16 redetection, newly detected HPV infections, and loss of HPV DNA detection during follow-up. We analyzed data from 2462 unvaccinated Brazilian women. HPV16 IgG and neutralizing antibodies at baseline were assessed by enzyme-linked immunosorbent assay (n = 1975) and by the pseudovirus-based papillomavirus neutralization assay (n = 487). HPV detection, genotyping, and viral load were assessed by PCR-based methods. The associations were analyzed by Cox proportional hazards models. We observed a positive association between HPV16 IgG seroreactivity and redetection of HPV16 infections. Age-adjusted hazard ratios (HR) with 95% confidence intervals (CI) ranged from 2.45 (1.04–5.74) to 5.10 (1.37–19.00). Positive associations were also observed between HPV16 IgG antibodies and (1) newly detected HPV infections by genotypes unrelated to HPV16 (age-adjusted HR [95% CI] = 1.32 [1.08–1.2]) and (2) loss of detection of HPV infections by genotypes unrelated to HPV16 (age-adjusted HR [95% CI] = 1.24 [1.03–1.50]). Naturally developed HPV16 antibodies do not prevent recurrent HPV infections. Overall HPV16 IgG and neutralizing antibodies seem to be serological markers for latent or past infections.
Keywords: HPV16; IgG; neutralizing antibodies; persistence; redetection; reinfection